Effect of texturized soy protein on quality characteristics of beef samosas - Mary Omwamba; Symon M. Mahungu; Abdul K. Faraj (International Journal of Food Studies)
Texturized soy protein (TSP) granules obtained from defatted soy flour were used to replace beef at 25, 50, 75 and 100% levels in samosa stuffing. The moisture, protein and ash content of the stuffing increased with an increase in the amount of texturized soy protein while the fat content decreased significantly (p<0.05) with an increase in the amount of texturized soy protein. Sensory evaluation of baked samosas showed no significant (p>0.05) difference in appearance, taste and overall acceptability with inclusion of texturized soy protein. However there were significant (p<0.05) differences in flavour, texture and willingness to purchase between 100% beef and 100% TSP samosas. There was a reduction in the moisture content while the protein, fat, ash and carbohydrate content increased in baked as compared to raw samples, both in the control and TSP50 samosas. The caloric value of the baked samosas was 24.07% lower in TSP added samples compared to 100% beef samples (control). Lipid oxidation increased with storage time from 0.25 to 0.68 mg malonaldehyde/kg in the control and from 0.21 to 0.39 mg malonaldehyde/kg in TSP50 samosas. The oxidation in the control was significantly (p<0.05) higher than in TSP50. The results suggest that TSP granules can be use with up to 50% addition in samosa products without significant differences in sensory attributes.